Changing landscape of dialysis withdrawal in patients with kidney failure: Implications for clinical practice. Issue 7 (6th March 2022) - Chen, Jenny H. C.; Lim, Wai H.; Howson, Prue
Abstract: Dialysis withdrawal has become an accepted treatment option for patients with kidney failure and is one of the leading causes of death in patients receiving dialysis in high‐income countries. Despite its increasing acceptance, dialysis withdrawal currently lacks a clear, consistent definition. The processes and outcomes of dialysis withdrawal have wide temporal and geographical variability, attributed to dialysis patient selection, influence from cultural, religious and spiritual beliefs, and availability of kidney replacement therapy and conservative kidney management. As a complex, evolving process, dialysis withdrawal poses an enormous challenge for clinicians and healthcare teams with various limitations precluding a peaceful and smooth transition between active dialysis and end‐of‐life care. In this review, we examine the current definitions of dialysis withdrawal, the temporal and geographical patterns of dialysis withdrawal, international barriers in the decision‐making process (including dialysis withdrawal during the COVID‐19 pandemic), and gaps in the current dialysis withdrawal recommendations for clinical consideration and future studies. SUMMARY AT A GLANCE: This review consolidates some of data around the definitions and challenges of withdrawing dialysis. It explores differences in global interpretation of the concepts and practice, and touches upon how COVID‐19 has influenced this subject.